Novel nanoparticle-based therapy to eradicate Pseudomonas aeruginosa infections in cystic fibrosis lungs: dual drug release by cubosomes - Sousa, Ana Margarida Rodrigues (2017)
Book of Abstracts of CEB Annual Meeting 2017